2015
DOI: 10.3390/en8053403
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Napier Grass as a Feedstock for Thermochemical Conversion

Abstract: Study on Napier grass leaf (NGL), stem (NGS) and leaf and stem (NGT) was carried out. Proximate, ultimate and structural analyses were evaluated. Functional groups and crystalline components in the biomass were examined. Pyrolysis study was conducted in a thermogravimetric analyzer under nitrogen atmosphere of 20 mL/min at constant heating rate of 10 K/min. The results reveal that Napier grass biomass has high volatile matter, higher heating value, high carbon content and lower ash, nitrogen and sulfur content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 41 publications
(54 reference statements)
8
65
0
Order By: Relevance
“…No noticeable peak was observed in this region and consequently, it can be deduced that lignin content of NGS has uniform thermal decomposition. The decomposition temperature values are in good agreement with literature values of 373 to 523 K, 523 to 623 K, 623 to 773 K, and above 773 K for extractives, hemicellulose, cellulose, and lignin correspondingly (Raveendran et al 1996;Reddy et al 2009;Mohammed et al 2015b;Mohammed et al 2015c). Structural analysis revealed that NGS has 12.07% extractives, 38.75% cellulose, 19.76% hemicellulose, and 26.99% lignin.…”
Section: Feedstock Characteristicssupporting
confidence: 78%
“…No noticeable peak was observed in this region and consequently, it can be deduced that lignin content of NGS has uniform thermal decomposition. The decomposition temperature values are in good agreement with literature values of 373 to 523 K, 523 to 623 K, 623 to 773 K, and above 773 K for extractives, hemicellulose, cellulose, and lignin correspondingly (Raveendran et al 1996;Reddy et al 2009;Mohammed et al 2015b;Mohammed et al 2015c). Structural analysis revealed that NGS has 12.07% extractives, 38.75% cellulose, 19.76% hemicellulose, and 26.99% lignin.…”
Section: Feedstock Characteristicssupporting
confidence: 78%
“…Paddy RH, Napier grass stem (NG) and sago biomass (SGW) was collected from a rice processing mill Sungai Besar, Selangor, Crop for the Future research Centre Semenyih Selangor and sago flour process plant effluent Pusa Sarawak respectively. Proximate and ultimate analyses were performed according to standard analytical methods [33]. The feedstock composition used was varied according to the scenario summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Moisture, ash content, and volatile matter were determined according to ASTM E1756–08, ASTM E1755–0, ASTM E872–82 standards. Fixed carbon was calculated by subtracting the percentage of ash composition and volatile matter from the dry sample mass . Elemental compositions of all the biomass samples were determined using a Flash 2000 CHNS/O analyzer (Thermo Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%